An Imperceptible Plastic Electronic Wrap. (20th October 2014) - Drack, Michael; Graz, Ingrid; Sekitani, Tsuyoshi; Someya, Takao; Kaltenbrunner, Martin; Bauer, Siegfried
<x xml:space="preserve">Abstract</x> Extremely compliant sub‐2‐μm sensor films enable temperature mapping on complex 3D objects, like integrated circuits on printed circuit boards, food packages, and on human skin. In their stretchable form, these metal films withstand strains up to 275%. This imperceptible electronic foil technology platform offers new avenues for the design of complex, hybrid rigid‐island stretchable‐interconnect electronic devices such as RGB light‐emitting diode (LED) strips that can be stretched and twisted without impairing their function. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>